On IVF Approximating Spaces - Dingwei Zheng; Rongchen Cui; Zhaowen Li (Journal of Applied Mathematics)
We introduce the concept of IVF approximating spaces and obtain decision conditions that every IVF topological space is an IVF approximating space.